The use of psycho-education based on the CBT protocol using a single-session virtual exposure within the psychological support of students with a fear of public speaking: results of a pilot study - Avramchuk Олександр; Ostryzhko Юлія (Psychosomatic Medicine and General Practice, 2020)
Introduction. Anxiety and fear of public speaking are some of the common complaints of students during their studies. The prevalence and consequences for psychological well-being make it possible to discuss the fear of public speaking in the context of pathopsychological changes that contribute to or are a variant of a social anxiety disorder. At the same time, constant anxiety and emotional distress can contribute to the development of other comorbid pathologies such as depressive disorder, other anxiety disorders, or substance abuse as a way of coping anxiety. The development and implementation of effective psychological/psychotherapeutic interventions for self-help and psychological support with using a virtual environment has already proven itself in dealing with specific phobias and other anxiety states and can be applied in preventative measures for social anxiety disorder among students. Aim. Investigate the impact of psychoeducation based on CBT protocol with a one-session virtual exposure on the level of students’ social anxiety before public speaking and the features of social interaction during education. Methods. Social anxiety assessment using the Social Phobia Inventory (SPIN), and Social Phobia Rating Scale (SPRS), clinical semi-structured interview, observation, and assessment of changes in virtual exposure. Results. Compared with the control group, there was a statistically significant decrease in all indicators on the SPIN (p <0.001) and SPRS (p <0.001) scales in the experimental group 1 month after virtual exposure. Decreases in social anxiety on the SPIN scale before the intervention and one month after were statistically different depending on belonging to the experimental group (F = 5.06, p = 0.035) and time (F = 5.46, p = 0.029), and significantly from a baseline level of social anxiety (F = 124.8, p = 0.000). The significance of changes in the experimental group as a whole on the SPIN scale is achieved by reducing the indicator in the subgroup with a high level of social anxiety, where statistical significance is significant p <0.001. Differences in changes in the level of social anxiety on the SPRS scale before the intervention and one month after, depending on belonging to the experimental group (F = 9.39, p = 0.006), time (F = 12.33, p = 0.002) and baseline level of social anxiety (F = 12.06, p = 0.000) are also significant. According to the SPRS method, a statistically significant decrease in the rate of exhaustion and overall restriction imposing social anxiety (p <0.001) was found in the experimental group and a statistically significant decrease in the using of part of strategies avoidance behaviors and the influence of typical unproductive beliefs (p <0.05, in accordance). Conclusion. Using psychoeducation based on CBT protocol with a one-session virtual exposure has proven to be an effective way of reducing the fear of public speaking. After 1 month undergoing a psychoeducational session using virtual exposure, a significant decrease in the intensity of anxious feelings, the impact of unproductive beliefs, and changes in behavior that underpinned them were revealed. It was noted that the most significant effect was achieved in the subgroup of participants with high input levels of social anxiety and manifest traits corresponding to the criteria of social anxiety disorder. Such changes may be explained by the need and timeliness of providing psychological support to this category of participants. Given that our findings are incomplete, they require further research and expansion of the experimental base.